KEEFEKTIFAN PEMBINAAN WARGA BINAAN KASUS PEMBUNUHAN DI LAPAS PEREMPUAN KELAS II A SUNGGUMINASA KABUPATEN GOWA - Nur Nashri Rahman; Irsyad Dahri; Heri Tahir (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract: This study aims to determine: 1) To find out the implementation of fostering inmates in a homicide case in the Class II A Women's Prison, Sungguminasa, Gowa Regency. 2) To find out what are the obstacles faced by the Class II A Women's Prison, Sungguminasa, Gowa Regency in fostering the inmates of the homicide case. This type of research is qualitative using data collection techniques through interviews and documentation. The data obtained from the interviews and documentation were then processed using qualitative descriptive analysis techniques. The results of this study indicate that: 1) The implementation of fostering the inmates of the homicide case in the Class II A Women's Prison Sungguminasa, Gowa Regency can be said to be effective, with the form of coaching, namely: (1) Skill development consisting of; Sewing, salon, crafts, gardening and catering. (2) Spiritual development, namely Pesantren An-nisa. (3) Physical development, namely morning exercise. 2) The obstacles faced by the Class II A Sungguminasa Women's Prison, Gowa Regency in fostering the inmates of the homicide case, are divided into two, namely: (1) Internal obstacles consisting of facilities and infrastructure that need to be added, human resources that need to be increased in number and increased in capacity, and the inmates themselves who need to increase their awareness. (2) External barriers, namely the location of the Class II A Sungguminasa Prison, Gowa Regency, which is felt by outsiders to be quite far away, both complained by the families of the inmates, as well as other outside parties who cooperate with the Class II A Sungguminasa Prison, Gowa Regency in every activity.